2017
DOI: 10.1177/0954405416683738
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of effects of MgO ratio on the surface quality and tool wear in turning Al–MgO composites

Abstract: In this study, specimens of Al-MgO metal matrix composites with reinforcement-volume ratios of 5%, 10% and 15% were produced using vacuum infiltration method. The produced specimens were then tested for machining on computer numerical control lathe using carbide, cubic boron nitride and coated cubic boron nitride cutting tools. Machining tests were performed under dry cutting conditions with three different feed rates (0.075, 0.15 and 0.225 mm/rev), four different cutting speeds (150, 200, 250 and 300 m/min) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…After this sample, the 60C40G composite produced with 450 • C and 480 MPa shows the lowest specific wear rate. 6.…”
Section: Data Availability Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…After this sample, the 60C40G composite produced with 450 • C and 480 MPa shows the lowest specific wear rate. 6.…”
Section: Data Availability Statementmentioning
confidence: 99%
“…Investigations about combining the prominent aspects of metals to obtain new and versatile materials have gained momentum in the metal matrix composite (MMC) material field [1,2]. For MMC production, several metals can be used as a matrix or reinforcement material, such as aluminum, steel alloy, magnesium, brass, bronze, and cast irons [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the cubic boron nitride tools, the milling forces decreased when the cutting speed decreased, and the B4C reinforcement ratio increased. Pul [ 19 ] analyzed the machinability of MgO/Al composite with ratios of 5%, 10%, and 15% of MgO particles by turning. They found that the most favourable results were obtained with a MgO reinforcement ratio of 10 wt.% MgO and using carbide cutting tools.…”
Section: Introductionmentioning
confidence: 99%
“…9 Research works into improving or quantifying the machinability of MMCs that has been undertaken since the early 1970s. [10][11][12][13] This is especially useful since carbide inserts are cheaper, and tool wear starts relatively quickly, allowing the evaluation of different parameters in order to determine their machinability and suitability for critical conditions. This is also ideal for evaluating the effects of cooling methods under similar conditions.…”
Section: Introductionmentioning
confidence: 99%